2023
DOI: 10.1186/s42466-023-00265-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life in adults with epilepsy: a multicenter, cross-sectional study from Germany

Abstract: Background Assessment of quality of life (QoL) has become an important indicator for chronic neurological diseases. While these conditions often limit personal independence and autonomy, they are also associated with treatment-related problems and reduced life expectancy. Epilepsy has a tremendous impact on the QoL of patients and their families, which is often underestimated by practitioners. The aim of this work was to identify relevant factors affecting QoL in adults with epilepsy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 53 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, since a number of patients remain resistant to ASMs, it has been shown that the overall quality of life scores were statistically significantly higher in the group of patients who were responders as compared to nonresponders (28). In line with these findings, it has been also, recently, shown that the insufficient seizure control with high frequency of seizures is significantly related to the poor quality of life (25).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, since a number of patients remain resistant to ASMs, it has been shown that the overall quality of life scores were statistically significantly higher in the group of patients who were responders as compared to nonresponders (28). In line with these findings, it has been also, recently, shown that the insufficient seizure control with high frequency of seizures is significantly related to the poor quality of life (25).…”
Section: Discussionmentioning
confidence: 62%
“…However, considering the influence of epilepsy-related factors, it has to be emphasized that some of them also affect quality of life. Thus, it was shown that high seizure frequency might be associated with poorer quality of life (23,25), although these results are not fully consistent (26). It has been also…”
Section: Discussionmentioning
confidence: 96%
“…However, the relationship between post-operative quality of life and individual clinical variables is not clear. The literature contains studies that show a relationship between QoL and the frequency of seizures [ 42 ], age at epilepsy onset [ 23 ], and the severity of symptoms of depression and anxiety [ 42 , 43 , 44 ]; however, there are also studies in which this relationship was not demonstrated (age at epilepsy onset: [ 43 , 45 , 46 ]; seizure frequency: [ 43 ]. The present study did not show the association between post-surgical QoL and other analyzed demographical or clinical variables (which was similar to other studies) such as sex [ 46 ], age [ 47 ], education level [ 46 ], or number of prescribed antiepileptic drugs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences between patients with TSC and IGE were also determined for Neurological Disorder Depression Inventory for Epilepsy (TSC: 13.1; IGE: 11.2, P = 0.009) and Liverpool Adverse Events Profile scores (TSC: 42.7; IGE: 37.5, P = 0.017) with higher score and worse results for TSC patients in both questionnaires. syndrome [10,11,[18][19][20][21][22]. In the present analysis, only epilepsy patients diagnosed with either IGE or FE were included.…”
Section: Disease Cohort Datasets and Matchingmentioning
confidence: 99%